Top-Down Implementation of Mother Tongue-Based Multilingual Education from Grassroots Perspectives - Tañiza, Frolomea Narra; Kilag, Osias Kit; Andrin, Glenn; Groenewald, Elma; Abella, Julanie; Cordova Jr., Nelson (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
This study delves into the nuanced landscape of mother tongue-based multilingual education (MTB-MLE) implementation in the Philippines, examining the top-down policy execution from the bottom up. Through qualitative research methods, including interviews and focus group discussions, the study explores the perspectives of educators, parents, and community members. Four key findings emerged, highlighting the essential role of teacher preparedness and training in MTB-MLE success, the pivotal influence of community engagement, challenges posed by limited resources, and instances of adaptability and innovation in response to implementation hurdles. The study underscores the significance of ongoing professional development for educators, emphasizing the need for linguistic proficiency and pedagogical strategies aligned with MTB-MLE principles. Community involvement emerged as a determining factor, showcasing the active contributions of communities in the development of instructional materials, sharing linguistic expertise, and fostering positive language attitudes. Resource constraints posed challenges, calling for increased investments in the production of culturally relevant materials. Despite these challenges, the study reveals the resilience of stakeholders, leveraging technology and collaborative initiatives to overcome limitations. The findings contribute to the broader discourse on language-based educational reforms, providing insights for policymakers and educators navigating the complex terrain of MTB-MLE implementation. The study advocates for a comprehensive and adaptive approach that recognizes the intertwined dynamics of teacher preparedness, community engagement, resource availability, and innovative solutions to enhance the efficacy of MTB-MLE in the Philippines.